Bird diversity and noteworthy records from the western side of the Porculla Pass and the Huancabamba-Chamaya river sub-basin, northwest of Peru [with Erratum] - Saldaña, Irwing S.; División de Biogeografía y Conservación, Instituto de Ciencias Antonio Brack, Lima 15034, PERU Maria Koepcke Lab of Ornithology, Centro de Investigación en Biología Tropical y Conservación – CINBIOTYC, Calle Nestor Martos E 16, Piura 20004, PERU (2020)
Despite the great importance of the level of biodiversity and endemism that the EquatorialSeasonal Tropical dry Forest hosts, many of its areas remain unexplored. Here we present the resultsof the field evaluations carried out between 2014 and 2018 along the western side of the Porcullapass and the Huancabamba-Chamaya river sub-basin, in the northwest of Peru. this research is partof the dataset of the project Bird Assessments in Ecosystems of the Northwest of Peru – CINBIOTYC.We reported 170 bird taxa, belonging to 163 species and 32 families. Likewise, we reported twomigratory bird species, one boreal and one austral, four endemic of Peru, and 29 restricted-rangespecies, from which 25 belong to the Tumbesian Region, five to the Marañón Valley and one wasshared between them. We highlighted the record of four trans-Andean bird taxa, Amazilia amazilialeucophoea, Euphonia saturata, Basileuterus trifasciatus, and Pyrocephalus rubinus piurae, as well as, theremarkable records of Patagioenas oenops, Pachyramphus spodiurus, Turdus maranonicus, Incaspizaortizi, and the record of Thamnophilus bernardi at the east slope of the Andes (east of Porculla Pass).